الذكاء الاصطناعي والمؤسسات الناشئة دراسة تطبيقية حاضنة الأعمال جامعة الوادي - الزهرة بوعافية; جيهان مولاي; سولاف بوليفة (university of eloued جامعة الوادي, 2025)
"تهدف هذه الدراسة إلى تحديد مدى قدرة المؤسسات الناشئة على تبني الذكاء الاصطناعي، حيث أجريت الدراسة بحاضنة أعمال جامعة الوادي ونصت فرضية الدراسة على وجود علاقة بين قدرة المؤسسات الناشئة على تبني الذكاء الاصطناعي، حيث اعتمدت الدراسة على الاستبيان كأداة لجمع البيانات من عينة الدراسة البالغة 50 طالبا، كما اتبع أسلوب المنهج الوصفي التحليلي لتحليل البيانات والتي تم الحصول عليها وتحليلها من خلال استخدام برنامج spss. وخلصت الدراسة إلى جملة من النتائج أبرزها: • أن المؤسسات الناشئة ليس لديها القدرة الكافية على تبني الذكاء الاصطناعي وذلك راجع لعدة أسباب منها: قلة الوعي والمعرفة بأهمية الذكاء الاصطناعي، ضعف البنية التحتية وارتفاع تكاليف برامج وأجهزة الذكاء الاصطناعي؛ • كما تبين أن هناك ارتباط طردي بين المؤسسات الناشئة وقدرتها على تبني الذكاء الاصطناعي حيث انه كلما زاد تبني الذكاء الاصطناعي كلما زاد التحسن في المؤسسات الناشئة وزادت فرص نجاحها؛ • تعتبر الشفافية في تطبيقات الذكاء الاصطناعي ركيزة أساسية لتعزيز الثقة بين المؤسسات والمتعاملين؛ • من خلال تطبيق الذكاء الاصطناعي يمكن تحسين حماية أنظمة الكمبيوتر والشبكات والبيانات المهمة للمؤسسة من المخاطر التي قد تتعرض لها عبر الأنترنت. "This study aims to determine the extent to which startups are capable of adopting artificial intelligence. The study was conducted at the business incubator of El Oued University and was based on the hypothesis that there is a relationship between startups’ ability to adopt artificial intelligence. A questionnaire was used as the main tool for data collection, targeting a sample of 50 students. The study followed a descriptive-analytical methodology, and the collected data were analyzed using SPSS software. The study reached several key findings, the most notable of which are: • Startups generally lack sufficient capacity to adopt artificial intelligence. This is due to several factors, including limited awareness and understanding of AI’s importance, weak infrastructure, and the high costs associated with AI software and hardware; • A positive correlation was found between startups and their ability to adopt artificial intelligence. The more AI is adopted, the greater the improvement and the higher the chances of success for these startups; • Transparency in AI applications is considered a fundamental pillar in strengthening trust between organizations and stakeholders; • The application of artificial intelligence can enhance the protection of computer systems, networks, and critical organizational data from online threats;
ماستر
Keywords: ذكاء اصطناعي; مؤسسات ناشئة; حاضنات الأعمال; حاضنات الأعمال الجامعية; Artificial Intelligence; Startups; Business Incubators; University Business Incubators.